FAKTOR INTERNAL YANG MEMPENGARUHI CYCLE EFFECTIVENESS (CE) PADA PABRIK GULA MADUKISMO - Halleina Rejeki Putri Hartono (JAMER : Jurnal Akuntansi Merdeka, 2021)
This study aims to examine internal environmental factors that can affect the level of Cycle Effectiveness (CE) in the sugar production process at the Madukismo Sugar Factory (PG Madukismo). This research is a qualitative research using descriptive analysis method. The data used in this study are primary data and secondary data. The instrument in this study was an interview question conducted to PG Madukismo regarding internal environmental factors that influenced CE at PG Madukismo. The research data technique used observation techniques, interviews, archival data interviews. The technique of analyzing research data through three stages, namely data reduction (data reduction), data presentation (data presentation), and drawing conclusions and levers (drawing conclusions / verification). The results showed that the internal factors that influenced CE were the activity of measuring sugarcane weight, sugarcane delivery, crystallization and stopping milling. Production processes that have non-value added activities that occur in moving activities, waiting activities, and reworking activities.